Analisis Komunikasi Sosial dan Bahasa dalam Skenario Fiktif Squid Game Season 3: Pendekatan Teori Reduksi Ketidakpastian - Inosensius Enryco Mokos; Salehudin Salehudin (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This article examines the intricate dynamics of social communication and language within the recently released Squid Game Season 3, focusing intensely on how participants attempt to navigate and manage complex interpersonal relationships while subjected to extreme duress and fatal competition. Employing the Uncertainty Reduction Theory (URT) as its core analytical framework, this study systematically explores the immense challenges players encounter in establishing mutual trust, forming reliable alliances, and accurately interpreting often-deceptive verbal and non-verbal cues within an environment meticulously designed to breed suspicion and intense rivalry. The hypothetical scenarios developed for Squid Game Season 3 reveal how the inherent and manufactured uncertainty of the game, amplified by deliberate strategic deception and systematic manipulation perpetrated by both fellow players and the game organizers, severely impedes all forms of effective communication and voluntary cooperation. Crucially, the analysis identifies that the consistent failure to adequately reduce cognitive and behavioural uncertainty regarding others significantly contributes to players' profound isolation and extreme vulnerability, thereby directly and often fatally impacting their core survival strategies and crucial in-game decisions. Ultimately, this comprehensive theoretical analysis provides valuable insights into fundamental human communication behaviour when placed in high-stakes, zero-sum, life-or-death contexts, highlighting communication's critical role as both a survival tool and a catastrophic vulnerability.